171k views
5 votes
X1+x2=3 x1•x2=-7 quadratic equation answer please​

User GaetanoM
by
4.7k points

1 Answer

4 votes

Answer:

x² - 3x - 7 = 0

Explanation:

To write a quadratic equation with given roots, use this:

x² - (x1 + x2)x + (x1.x2) = 0

or

x² - (sum of roots)x + (product of roots) = 0

So substitute the given with sum of 3 and product of -7.

x² - (3)x + (-7) = 0 (simplify)

x² - 3x - 7 = 0

User Jonhoare
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.